Anaerobic capacity, isometric endurance, and Laser sailing performance - Vangelakoudi, A.; Vogiatzis, I.; Geladas, N. (Journal of Sports Sciences, 2007)
Laser sailors have to tolerate fatiguing contractions of the lower-body muscles for prolonged periods. The aims of the present study were (1) to evaluate the difference between top-ranked and club sailors, in their capacity to resist fatigue during sustained isometric and maximal power exercise, and (2) to examine the relationships between the above parameters and performance on a Laser simulator and competitive racing performance according to the national ranking list. Eight Greek nationally ranked Laser sailors were compared with eight club sailors. Each sailor performed: (a) an effort to the limit of tolerance on the Laser simulator, (b) an effort to the limit of tolerance of isometric endurance for the right leg on an isokinetic dynamometer, and (c) a Wingate test of maximal lower-body anaerobic power on a cycle ergometer. In the nationally ranked sailors, isometric endurance time (mean 160 s, s = 50) and endurance time on the Laser simulator (1381 s, s = 1354) were significantly (P < 0.05) longer than in the club sailors (101 s, s = 29 and 565 s, s = 367, respectively), whereas the final minute heart rate (in both groups: 149 beats · min-1, s = 22) and the mean arterial pressure (nationally ranked sailors: 129 mmHg, s = 16; club sailors: 120 mmHg, s = 21) on the Laser simulator were not different between groups. During the Wingate test, the nationally ranked sailors had a significantly lower index of fatigue (42%, s = 5) than the club sailors (49%, s = 6). Isometric endurance time was significantly correlated with the Wingate index of fatigue (r = -0.73; P < 0.001). The nationally ranked sailors' mean and maximal anaerobic powers were significantly correlated with their national ranking positions (r = -0.83 and -0.71, respectively). It is suggested that isometric endurance and anaerobic power are well-developed in Laser class sailors and may influence their sailing performance. Furthermore, compared with club sailors, the nationally ranked sailors are able to sustain the same intensity of lower-limb isometric contractions for much longer with similar cardiovascular responses.